NON SURGICAL MANUAL REMOVAL OF FRACTURED ENDODONTIC INSTRUMENT IN THE APICAL THIRD OF MAXILLARY PREMOLAR: CASE REPORT - Izabela Volpato Marques Tookuni; Marcelo Capitanio; Heitor Jefferson Sevila Versan; Marcos Sergio Endo (Portal de Periódicos da Marinha do Brasil, 2020)
Accidental fracture of an instrument during endodontic treatment can occur due to lack of dental anatomy knowledge, use of inadequate instruments or technical failure of the operator. The aim of the present study is to present a case report of instrument fragment removal from a superior premolar. The fragment was identified to be in the apical third of the buccal root. The first attempt to remove the instrument was made without success. After 15 days, in a new attempt, the instrument was removed with the aid of an ultrasonic endodontic tip. The intracanal medication between sessions was calcium hydroxide, camphorated paramonochlorophenol and propylene glycol. After more 15 days, the tooth was asymptomatic and was filled by lateral condensation. Thus, the patient was referred for definitive restoration. After 3 months, it was observed radiographically the regression of the periradicular lesion. In conclusion, the removal of the fragment proved to be an efficient option, providing the maintenance of the tooth with no signs and symptoms.